Camouflage Orthodontic Treatment for Skeletal Prognathic with Anterior Openbite - Herlia Nur Istindiah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
An ideal treatment is an orthognathic surgery for patients having prognathi skeletal with crossbite and openbite anterior. When a patient chooses camouflage treatment, the treatment applied is upper anterior dental proclination, lower anterior dental retroclination, and upper and lower incisive extrusion. Limitation of camouflage treatment results in the need to heed etiological factors and patient complaints. Treatment of prognati skeletal and Class III dental (Angle) cases accompanied by skeletal type openbite anterior and crossbite anterior on a female patient aged 32. Orthodontic treatment using a pre-adjusted system and palatal crib. Type of anchorage for moderate upper and maximum lower dental arc. The position of the upper anterior dental bracket is installed 0.5 mm toward the gingival. Anterior dental protraction with protraction arch. Removal of 34 and 44 to retract lower anterior dental. Openbite anterior is corrected by upper anterior dental extrusion using extrusion arch and elastic vertical. After 26 months of treatment, the treatment goal is achieved, i.e., 2 mm overjet and overbite, better smile incisal display, and lowered concave profile. In a patient with camouflage orthodontic treatment, improvement occurs mostly at dental. Use of palatal crib provides an opportunity for upper anterior dental extrusion and lower anterior dental movement to lingual. The success of camouflage treatment occurs when esthetic and dental are not compromised to get good occlusion. To get stability, the dental movement must heed the position of supporting tissues.